Cathepsin activities and thermal properties of Nile tilapia (Oreochromis niloticus) meat during ambient storage - Nonthaput, Tulakhun; Hahor, Waraporn; Thongprajukaew, Karun; Yoonram, Krueawan; Rodjaroen, Somrak (Agriculture and Natural Resources, 2017)
Understanding the postmortem changes at ambient aquatic temperature can be useful for estimating the time of death in environmental forensic studies when little information is available. Muscle degradation was investigated in Nile tilapia (Oreochromis niloticus) in terms of the specific activities of cathepsins (B, H and L) and the scavenging activities and thermal transition properties of myosin and actin, to assess postmortem changes with time (0, 1, 2, 4, 8, 12, 24 and 48 h after death). The study results are relevant to ambient temperatures in Thailand, (about 30 oC). The specific activities of the three cathepsin enzymes increased significantly with postmortem time (p < 0.05) and had a highly significant positive relationship (r = 0.987-0.997, p < 0.01, n = 32). Cathepsin H had the lowest specific activity and exhibited a different type of time profile. Its lowest specific activity was observed at 8 h, which indicated a significant role at this point in time after death. The radical scavenging activities substantially decreased with the time since death, especially within the first 1 h, while no changes occurred from 2 to 8 h, or from 12 to 24 h. The thermal properties of myosin and actin were observed up to a 24 h delay. The degradation of each protein fluctuated with the delay time; actin was more sensitive to postmortem delay than myosin. Overall, the findings from the current study might be used as primary data to estimate the time of death of an aquatic animal. A potential application is for environmental forensics in relation to fish kill events associated with pollution crimes or the mass death of exported fish under transportation insurance, as well as in animal cruelty investigations.